3D Printing Materials for Soft Robotics. Issue 19 (9th November 2020) - Sachyani Keneth, Ela; Kamyshny, Alexander; Totaro, Massimo; Beccai, Lucia; Magdassi, Shlomo
Abstract: Soft robotics is a growing field of research, focusing on constructing motor‐less robots from highly compliant materials, some are similar to those found in living organisms. Soft robotics has a high potential for applications in various fields such as soft grippers, actuators, and biomedical devices. 3D printing of soft robotics presents a novel and promising approach to form objects with complex structures, directly from a digital design. Here, recent developments in the field of materials for 3D printing of soft robotics are summarized, including high‐performance flexible and stretchable materials, hydrogels, self‐healing materials, and shape memory polymers, as well as fabrication of all‐printed robots (multi‐material printing, embedded electronics, untethered and autonomous robotics). The current challenges in the fabrication of 3D printed soft robotics, including the materials available and printing abilities, are presented and the recent activities addressing these challenges are also surveyed. Abstract : The progress in 3D printable materials for soft robotics is reported, emphasizing high‐performance materials such as flexible and stretchable materials, selfhealable materials, and shape memory polymers. The challenges in fabrication of an all‐printed soft robots, including multi‐material printing, embedded electronics, and untethered and autonomous robots, are elaborated as well as the challenges and approaches for modeling these soft systems.